PERAN PEKERJA SOSIAL DALAM PENDAMPINGAN ANAK SEBAGAI SAKSI PADA PROSES PERADILAN PIDANA DI PENGADILAN NEGERI KLAS I A PADANG - Tanjung, Lifiana (UNES Law Review, 2018)
Professional Social Workers according to Article 1 paragraph (14) of Law Number 11 of 2012 on the Criminal Justice System of Children in the Class IA Court of Padang the child as a witness has been damping by social workers but in practice not all children who witnessed accompanied by social workers the. The problem discussed is how the role of Social Worker in Child assistant as Witness and constraint and optimization of social worker role in child assistance as witness to criminal justice process in Class Court of First Class A Padang Specification of this research is analytical descriptive research with sociological juridical approach. The data used are primary data and secondary data, The data obtained are analyzed qualitatively and presented in the form of analytical descriptive. Based on the research result, the role of social workers in assisting the child as witness in the judiciary is to make the child social report to be used as the guidance of the court hearing. Social workers should be able to make children express opinions and express themselves freely. Listen to the child's opinion of a criminal incident he / she has heard, seen and experienced by himself / herself. Social Workers should create an atmosphere of discussion that does not make children more cornered. The obstacles faced by social workers in their role as witness counselors are the limited number of social workers, scholarly backgrounds or non-supportive counselors, lack of cooperation network, time of implementation of assistance that is sometimes not in accordance with the plan, has no shelter for children so it should find a place of reference for the child. Optimizing the role of social workers in assisting children as witnesses is to equip judges on the understanding of social research